Integration of Workplace Readiness Skills into Tourism Educational Curriculum for Graduates’ Employability - Mohd Shariff, Nurhazani (Management Research Journal, 2021)
Tourism education has grown quite rapidly in line with the industry development today. Several valuable skills need to be highlighted by the educational institutions in order to produce tourism graduates with quality and efficient employability for future working environment. One of the essential skills needed by the graduates for future employability is workplace readiness skills. Taking the higher education in Malaysia as a case study, the objective of this study is to identify workplace readiness skills required by the industry to be integrated into the tourism educational curriculum for graduates’ employability. This study surveyed 100 tourism sectors in Malaysia consisted of travel agents, restaurants, hotels and transportation sectors using quantitative method. Six domains represented the workplace readiness skills have been identified namely basic skills, using technology skills, practicality skills, business orientation skills, planning and organizing skills and self-management skills. The findings indicated that workplace readiness skills are important to be integrated into the tourism educational curriculum. It was also noted that tourism education needs to integrate the practicality skills and planning and organizing skills into the course curriculum. This study contributes to the higher education in designing and preparing tourism education taking into account the workplace readiness skills to enhance graduates’ employability. It further indicates the needs of collaboration between higher education and industry for future graduates’ employability within the competitive environment.